Examining isotonic and isometric exercises for post-activation performance enhancement in kickboxers upper limb strength and power - Liang Wang; AnQiang Hu (Scientific Reports)
Abstract Maximizing muscular performance to improve upper limb strength and power can be advantageous in preparing kickboxers for training and competition. The objective of this study was to evaluate the influence of isometric and isotonic upper limb post-activation performance enhancement (PAPE) strategies on the maximal strength of young men kickboxers’ upper limbs, assessed through handgrip strength (HG) and the chest medicine ball throw test (CMBT). Fifty-three amateur men kickboxers, aged between 16 and 23, participated voluntarily in this regional-level study. Over two weeks, participants were randomly exposed to three conditions: isometric, isotonic, and control (no warm-up) conditions. Each condition was repeated twice during this timeframe, resulting in six data collection sessions. After each condition, participants underwent assessments for HG strength and CMBT performance. Repeated measures ANOVA revealed significant differences between conditions in HG (p < 0.001; ES = 0.740). Post-hoc analysis revealed that the isometric condition showed significantly better scores compared to both the isotonic condition (p < 0.001) and the control condition (p < 0.001). Significant differences were found in CMBT (p < 0.001; ES = 0.355). Post-hoc analysis revealed that the isometric (p < 0.001) and isotonic conditions (p < 0.001) displayed significantly superior outcomes in contrast to control. In conclusion, isometric exercise significantly improved maximal HG strength and muscular power in the CMBT, showing a potential effective strategy for implementing PAPE for kickboxers.